Acute renal failure associated with vancomycin and β‐lactams for the treatment of osteomyelitis in diabetics: piperacillin–tazobactam as compared with cefepime. (21st November 2013) - Moenster, R. P.; Linneman, T. W.; Finnegan, P. M.; Hand, S.; Thomas, Z.; McDonald, J. R.; Grobusch, M.
Abstract Few data are available on the nephrotoxic potential of vancomycin when combined with certain β‐lactam antibiotics for the treatment of osteomyelitis (OM). A retrospective cohort study was conducted of all diabetic patients with OM treated with vancomycin plus piperacillin–tazobactam (VPT) or vancomycin plus cefepime (VC) for at least 72 h at a VA Medical Center between 1 January 2006 and 31 December 2011. All patients with a creatinine clearance (CrCl) of ≤40 mL/min, a blood urea nitrogen/serum creatinine (SCr) ratio of ≥20 : 1 or an absolute neutrophil count of <500 cells/mm3 were excluded. The primary outcome was development of acute renal failure (ARF), defined as an increase in SCr of 0.5 mg/dL or 50% of baseline. One hundred and thirty‐nine patients met the inclusion criteria; 109 in the piperacillin–tazobactam group and 30 in the cefepime group. Among patients receiving VPT, 29.3% (32/109) developed ARF, as compared with 13.3% (4/30) receiving VC (p 0.099). Among patients receiving high‐dose therapy (≥18 g of piperacillin–tazobactam daily or ≥3 g of cefepime daily), 37.5% (9/24) receiving VPT and 17.6% (3/17) receiving VC developed ARF (p 0.29). A multiple logistic regression analysis identified weight and average vancomycin trough as the only significant predictors of ARF; the choice of VPT as therapy yielded an OR of 3.45 (95% CI 0.96–12.40; p 0.057). The authors were unable to detect a statistically significant difference in ARF between groups; however, the power requirement was not met. Further study with a larger patient population seems warranted.